Phenotypic integration : studying the ecology and evolution of complex phenotypes - Pigliucci, Massimo, 1964-; Preston, Katherine (Katherine A.) (OUP E-Books., 2004)
The interface of evolution and development has attracted the attention of evolutionary and developmental biologists, geneticists, and organismal biologists. Pigliucci (ecology, evolutionary biology, University of Tennessee) and Preston (botany, Standford University) bring together work by experts in the field of phenotype integration, shedding ligh.